IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF GROUP TYPE IN INCREASING LEARNING RESULT OF MATH - Rezki Novianti (Universitas Negeri Makassar, 2017)
This study aims to determine the improvement of students' mathematics learning outcomes through the enforcement of cooperative learning model of mobile type of kelmpok in grade IX students of SMP Negeri 6 Bambang Kabupaten Mamasa. This study is a classroom action research conducted in the odd semester of 2016/2017 with the subject of research as many as 32 students. This research was conducted in two cycles. Data collection techniques are carried out with learning outcomes at each end of the cycle and observation sheets to see what needs to be maintained and need to be improved as part of the reflection. The collected data was analyzed by using descriptive analysis. The results of this study showed that: (1) the average of the learning outcomes of mathematics cycle I was 62.28 with the standard deviation of 10.77, was in the medium category, and did not meet the criteria of classical mastery. (2) the average of students' mathematics learning outcomes in cycle II is 71,41 with standard deviation of 9.94, is in high category, and has fulfilled the criteria of classical completeness that is 87,5% from many students who are solved individually. Based on these results, it can be concluded that the application of cooperative learning model of group-type type can improve the learning outcomes of students of grade IX SMP Negeri 6 Bambang Kabupaten Mamasa